On the mechanism of methanol photooxidation to methylformate and carbon dioxide on TiO2: an operando-FTIR study1. Issue 17 (7th May 2015) - El-Roz, Mohamad; Bazin, Philippe; Daturi, Marco; Thibault-Starzyk, Frederic
<x xml:space="preserve">Abstract</x> This work is a mechanistic study of total and partial methanol photooxidation using operando FTIR coupled to gas phase analysis techniques (gas-IR and MS).